Cofense: Malware Trends Q4 2019. Issue 2 (February 2020) - Unknown
Abstract : Although the title of this report uses the word 'trends', one is almost tempted to replace it with 'fashions'. Malware families and attack vectors wax and wane in popularity – presumably on the basis of whatever works best at any given time. And, as this report highlights, the use of malware is also subject to seasonal effects because, as the summary states, "even criminals take a holiday".